Tinjauan Yuridis Pemutusan Hubungan Kerja Sepihak oleh Perusahaan Kepada Pekerja pada Putusan No.36/G/2014/PHI Medan - Simanjuntak, Sari; Hasibuan, Abdul Lawali; Mubarak, Ridho (Jurnal Ilmiah Penegakan Hukum, 2017)
Juridical Review of  Unilateral Termination of Employment by the Company to the Worker on Putusan No.36/G/2014/PHI MedanDisputes or misunderstandings that cause layoffs are generally triggered by a lack of communication between workers and employers. The workers are positioned as the party in need, therefore the position of workers is very weak and vulnerable to irregularities. The problems in this study are: 1) How are the Government and the Company's Efforts Against Employee Layoffs? 2) What is the legal consideration of the judge in deciding unilateral termination of disputes by the company Decision Number: 36/G/2014/PHI.Mdn? This type of research is normative research,. In this case the Industrial Court in the Medan District Court decided to grant the Plaintiff's claim in part, stating that the working relationship between the defendant and the plaintiffs had never been terminated or continued, sentencing the defendant to reinstate the plaintiffs and place them in the original workplace, punishing the defendant for pay for forced money (dwangsoom).